STRATEGI PERSONAL SELLING SAHABAT_KOE PONSEL PEKANBARU DALAM MENINGKATKAN JUMLAH PELANGGAN DI KOTA PEKANBARU - Daulay, Muhammad Makruf Kamal; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Pekanbaru as the capital of Riau province, grow many kinds of business one of them Counter Mobile business. Counter Mobile now mostly found almost every corner place in Pekanbaru. The rising growth of Counter Mobile in Pekanbaru, makes the counter business creates creative and efficient promotional ideas in attracting audiences. Based on the phenomenon of counter in Pekanbaru more and more, making counter Sahabat_Koe Pekanbaru mobile phone trying to increase the number of customers in overcoming the problem of the decline in customers. Therefore researchers interested in conducting research with the aim to know the Personal Selling Strategy Sahabat_Koe Pekanbaru Mobile Phone In Improving Customer Number In Pekanbaru City. This research uses qualitative method, that is collecting data from field through observation, interview, and documentation. The subjects of this research are 1 manager, 1 assistant manager, 2 employees, and 1 customer and 3 prospective subscribers Sahabat_Koe Pekanbaru mobilephone selected based on purposive sampling technique and using interactive data analysis technique, while technique of examination of data validity through extension of participation and triangulation. The results of this study show first, prospecting sahabat_koe preparing a notebook; noting the name, address, and phone number of the prospect. Second, Pre approach opens a sales interview, informing potential benefits when using the product. Third, Approach knows how to meet and greet buyers and make the relationship a good start. Fourth, Presentation asks questions, makes sales presentations, focuses sales talks, compares products. Fifth, Handling Objection uses a positive approach, finding a hidden refusal and asking the buyer to explain any rejection. Sixth, Closing The salesperson must know how to recognize the cues for the closing of the transaction from the buyer, which includes the physical actions of comments and questions. Seventh, Follow Up sahabat_koe convince buyers about the interest of salespeople.